Board Diversity and Financial Performance in the Top 500 Australian Firms. Issue 4 (December 2015) - Vafaei, Alireza; Ahmed, Kamran; Mather, Paul
Abstract : Recent regulatory changes in Australia require listed companies to implement policies for increasing board diversity and to report thereon. In this paper we examine the association between gender diversity on corporate boards and the financial performance of a large sample of the top 500 listed companies in Australia during the period 2005–2011, addressing many of the methodological weaknesses in prior studies. Our descriptive statistics show that the proportion of female directors on boards increased markedly between 2010, when ASX amended principles came into effect, and 2011. The results also show that board diversity is positively associated with financial performance after controlling for a number of firm‐specific, ownership and governance characteristics and potential endogeneity with the two‐stage least square tests. Thus, we inform the policy debate by providing empirical evidence supporting the business case for board diversity.